Epidemiological study of road traffic injury victims attending a tertiary care centre in Hyderabad - Shadan Taj, Qurat Ul Ain; Anil Kumar, Karmakonda (International Journal Of Community Medicine And Public Health, 2020)
Background: Increased vehicular traffic on roads has now begun to cause road traffic accidents. Road traffic injuries will rise to become the fifth leading cause of death by 2030. In India every year road traffic accidents (RTA) accounts for over 1,00,000 deaths, 2 million hospitalization and 7.7 million minor injuries. The objective of the study was to study the socio-demographic profile and the epidemiological factors related to RTA. Methods: It is a cross-sectional, hospital based descriptive study done on all road traffic injury victims admitted at Owaisi hospital attached to deccan college of medical sciences between April 2013 and July 2014. 573 RTA victims were interviewed using a predesigned questionnaire. Results: Majority of the victims were from the age group of 25 to 39 years (38.4%). Majority are males (85.5%). Majority victims had a primary level of education (29.3%), followed by illiterates (20.6%). Majority victims were from upper lower socio-economic class (34.5%) and lower class (30.4%). Majority of the accidents occurred on weekends (57%). Maximum road traffic accidents (45%) occurred during rainy season. Majority of the road user victims were drivers (47%). Motorised two wheelers (43%) were the leading road users among the victims. Conclusions: Majority of the victims being in the productive age group. Public should be sensitized about the raise in road traffic accidents especially in peak hours and weekends. Motorcyclists being the leading road users among victims must be counselled regularly regarding proper road safety measures.